2017
DOI: 10.1016/j.biomaterials.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Past matrix stiffness primes epithelial cells and regulates their future collective migration through a mechanical memory

Abstract: During morphogenesis and cancer metastasis, grouped cells migrate through tissues of dissimilar stiffness. Although the influence of matrix stiffness on cellular mechanosensitivity and motility are well-recognized, it remains unknown whether these matrix-dependent cellular features persist after cells move to a new microenvironment. Here, we interrogate whether priming of epithelial cells by a given matrix stiffness influences their future collective migration on a different matrix – a property we refer to as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 33 publications
14
155
1
Order By: Relevance
“…Additionally, microRNA-21 has been shown to enhance levels of αSMA and fibrotic mechanical memory of stem cells (22). Our previous work showed that nuclear YAP localization due to stiff-priming of epithelial cells enhances their pMLC levels and migration speed in future soft ECMs (24). Based on these established connections between mechanosensitive transcription, nuclear-cytoskeleton factor production, and overall cellular response, we assume that cellular mechanoactivation ( ) leads to mechano-sensitive transcriptional activity, which leads to production of mechanosensitive mRNA (normalized levels are denoted by ).…”
Section: The Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, microRNA-21 has been shown to enhance levels of αSMA and fibrotic mechanical memory of stem cells (22). Our previous work showed that nuclear YAP localization due to stiff-priming of epithelial cells enhances their pMLC levels and migration speed in future soft ECMs (24). Based on these established connections between mechanosensitive transcription, nuclear-cytoskeleton factor production, and overall cellular response, we assume that cellular mechanoactivation ( ) leads to mechano-sensitive transcriptional activity, which leads to production of mechanosensitive mRNA (normalized levels are denoted by ).…”
Section: The Modelmentioning
confidence: 97%
“…Separately, miRNA-21 transcription and downstream MRTF signaling have been implicated in long-term memory in stem cells over several weeks (22). In the context of cell migration, we have recently shown that epithelial cell sheets primed on a stiff matrix for 3 days store mechanical memory through nuclear YAP localization, which continues to enhance cell migration through enhanced pMLC expression and focal adhesion formation on soft matrix for 2-3 days (24). Priming less than 3 days substantially reduces memory, which suggests that memory processes operate progressively over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a delayed response could well reflect a sustained effect after the abrogation of stretch, or as a result of "repairing" the monolayer after cyclic strain. Alternatively, this could be due to the mechanical memory of keratinocytes as reported recently [36,59]. Distinct behaviors and cellular properties between oral and skin keratinocytes have been appreciated and these include aspects of wound healing and angiogenesis [9,50,56].…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with mechanical memory, upon removal from stiffness, RUNX2 target transactivation was only gradually lost, concomitant with a gradual increase in PLIN1, an adipogenic biomarker (Fig.3g). YAP target expression did not persist similarly to RUNX2 targets (Extended Data Fig.9k), which was surprising since YAP has been linked to mechanical memory in epithelial cells 26 . However, despite being a wellestablished transducer of mechanical cues, YAP has no known gene bookmarking function 19,27 .…”
mentioning
confidence: 93%